(untitled) (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted during klwrij; sea.son 2012 to study the effect or organic manures and dift.rent levels of NPK on growth and quality of 8ottJe gourd. The experiment consisting of 16 treatments viz .. four levels of NPK (contro1. 100:50:50. 80:40:40 and 60:30:30) and organic manures (control. vermicompost. poultry manure and FYM) faclOriaJ designed in RBD with three replications. Resulls indicated that application of NPK (100:50:50) + vermicompost (5.0 c/ha) was recorded minjmum days taken to appearance of first female flower, maximum length of main vine (m). numbe.r of primary branches J>er vine. length and width of leaf (cm) 45 days after sowing. minimum node number at first female tlower appeared, protein content in fmic, cn1de fib1·e content in fmit, nitrogen concem in fruit, phosphorus con1enl io fruit, potaium content in fruit, yield q/ha and re1um rupee. investment.